REHABILITASI DAN PEMELIHARAAN PERLENGKAPAN JALAN DALAM HAL PEMETAAN SEBARAN PANEL KWH METER LAMPU PENERANGAN JALAN UMUM DI WILAYAH DESA MUNGGU - I Komang MULIARTA; Ida Kade Suarioka; I Komang Gede (Dharma Bhakti, 2023)
The importance of understanding activity procedures and data accuracy in the form of making maps that can provide convenience in studying an area. The aim is to train and broaden the horizons of students in developing creativity and problem solving, understanding an official administrative process and validating assets ownership of kwh meter public street lighting panels in the form of maps. With the observation method, surveys in order to understand information about the description of procedures for procurement and installation of street equipment and other strategic places, rehabilitation / maintenance, procurement of materials / components, and flowcharts for repairing public street lighting. Making a map with the Arcgis application, producing a map of the distribution of kwh meter panels for public street lighting lamps in the munggu village area, mengwi sub-district, badung district.